KENDALA DAN SOLUSI DALAM PEMBELAJARAN BAHASA INDONESIA BERBASIS KURIKULUM MERDEKA DI MTS NUR RAHMA KOTA BENGKULU - Juni Astuti, Dina Putri; Sonia, Gina; Dwika Gustiadri, Deni; Murni, Artati (Jurnal Ilmu Pendidikan Islam, 2025)
This research aims to identify obstacles and solutions in implementing the Independent Curriculum in Indonesian language learning at MTS Nur Rahma, Bengkulu City. The Merdeka Curriculum is designed to provide flexibility in learning, emphasizing a project-based approach, as well as the integration of technology in the teaching and learning process. However, in practice, the implementation of this curriculum faces various obstacles, such as teacher understanding that is not yet optimal, limited facilities and infrastructure, as well as resistance from students and parents. To overcome this challenge, various solutions are needed, including increasing teacher capacity through training and mentoring, procurement and optimization of facilities and infrastructure, as well as more intensive outreach to students and parents. With cooperation between the government, schools and the community, it is hoped that the implementation of the Independent Curriculum can run more effectively and provide maximum benefits for students.